2022
DOI: 10.3390/cells11233787
|View full text |Cite
|
Sign up to set email alerts
|

IL13 Promoter (−1055) Polymorphism Associated with Leukocyte Mitochondria DNA Copy Number in Chronic Obstructive Pulmonary Disease

Abstract: IL13 polymorphism is associated with chronic obstructive pulmonary disease (COPD). Patients with COPD have smaller numbers of mitochondria deoxyribonucleic acid copies (mtDNA-CN) than people without COPD do. However, whether IL13 polymorphism affects the mutation and recombination of mitochondria remains unclear. Data for patients with COPD and non-COPD were collected from Kaohsiung Chang Gung Memorial Hospital to enable a comparison of their leukocyte mtDNA-CN and the association of this information with IL-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Liu et al demonstrated that COPD patients have a lower leukocyte mtDNA copy number than nonsmoker or non-COPD patients [26]. His study also showed that the IL-13 promoter (−1055) polymorphism is associated with leukocyte mtDNA copy number [27]. The sequencing of a complete mitochondrial genome of a rat chronic obstructive pulmonary disease strain, with a length of 16,310 bp and coding for 13 protein-coding genes, two ribosomal RNA genes, and 22 transfer RNA genes, provides valuable insights into potential mitochondrial DNA mutations as markers in cancer and other diseases [28].…”
Section: Mtdna Mutations and Variations And Their Role In Copdmentioning
confidence: 96%
See 1 more Smart Citation
“…Liu et al demonstrated that COPD patients have a lower leukocyte mtDNA copy number than nonsmoker or non-COPD patients [26]. His study also showed that the IL-13 promoter (−1055) polymorphism is associated with leukocyte mtDNA copy number [27]. The sequencing of a complete mitochondrial genome of a rat chronic obstructive pulmonary disease strain, with a length of 16,310 bp and coding for 13 protein-coding genes, two ribosomal RNA genes, and 22 transfer RNA genes, provides valuable insights into potential mitochondrial DNA mutations as markers in cancer and other diseases [28].…”
Section: Mtdna Mutations and Variations And Their Role In Copdmentioning
confidence: 96%
“…Large-scale, multicenter studies are essential to validate findings and establish robust associations. Additionally, understanding the interactions between nuclear and mitochondrial genomes and their collective impact on COPD susceptibility requires further exploration [27]. As we delve deeper into the realm of mitochondrial genetics in COPD, integrating these insights with clinical parameters and environmental influences becomes crucial.…”
Section: Challenges and Future Directionsmentioning
confidence: 99%
“…IL-4 and IL-13 have many functions in the lungs, primarily in the regulation of inflammatory immune responses as well as mucus secretion [ [33][34][35][36]. Some genes, including IL13 polymorphism, have been associated with COPD [37,38] although studies are controversial. IL-13 binds to the IL-13 receptor alpha1 (IL-13a1) and induces recruitment of IL-4 receptor alpha 1 (IL-4Ra1), forming a complex responsible for the activation of signalling pathways [33].…”
Section: Anti Interleukin-4 and Interleukin-13mentioning
confidence: 99%